2005
DOI: 10.1038/sj.bmt.1704852
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infection in children after allogeneic stem cell transplantation: diagnosis, treatment and immunity

Abstract: Summary:Human adenoviruses (HAdV) are a frequent cause of potentially fatal infections in patients after allogeneic stem cell transplantation, especially in children. Monitoring of serum/plasma by real-time quantitative PCR is a sensitive tool for the recognition of patients at risk of a potentially fatal infection and for the evaluation of the efficacy of treatment. Data from a retrospective study and from a prospective study demonstrate that recovery of immunity after transplantation is essential for the eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
1
36
1
2
Order By: Relevance
“…29 In patients with viremia, reduction of immunosuppression and initiation of preemptive treatment with cidofovir has become the standard of care in many centers. 29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances.…”
Section: Discussionmentioning
confidence: 56%
“…29 In patients with viremia, reduction of immunosuppression and initiation of preemptive treatment with cidofovir has become the standard of care in many centers. 29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances.…”
Section: Discussionmentioning
confidence: 56%
“…12 Rather commonly, immunosuppressive treatment has been reduced, as reconstitution of the lymphocytic immune system is associated with viral clearance. [13][14][15] AdV-specific T cells have been detected in children after HSCT and seem to protect against AdV disease. 16 For this reason, immunotherapy with donor T cells has been suggested, and a novel approach using purified AdV-specific donor T cells is promising, although in need of further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that reconstitution of HAdV-specific T cells is essential to control HAdV infection after allogeneic SCT. [5][6][7][8][9] Manipulation of immune reconstitution by adoptive transfer of donor-derived HAdV-specific T cells may, therefore, be an effective strategy to provide shortand long-term antiviral protection.…”
Section: Introductionmentioning
confidence: 99%